Structure and Space Pattern in Gunungpati Sub-District: Space Utilization Evaluation Analysis - Al-Adly Darniyus; Hardi Warsono; Teuku Afrizal; Retno Sunu Astuti (Indonesian Academy of Social and Religious Research (IASRR), 2020)
This article focuses on the evaluation of regional spatial planning policies, namely the Regional Regulation of the City of Semarang Number 14 of 2011 concerning the 2011-2031 Regional Spatial Plan, particularly regarding the spatial structure and spatial patterns in the Gunungpati District. Because the issue of spatial planning has caused various environmental problems in urban areas. This article refers to the Regulation of the Minister of Agrarian and Spatial Planning Number 9 of 2017 concerning Guidelines for Monitoring and Evaluation of Spatial Use, using a literature study methodology approach. The results show that the spatial structure determination in Gunungpati District needs to be changed because of the emergence of settlements that are on quite /very sloping slopes. As a result, Gunungpati District as a conservation area, water catchment, and green catchment as well as protecting the area below has changed. Meanwhile, the network of facilities and infrastructure as well as green open space in Gunungpati District has met the requirements of the RTRW for Semarang City. Based on the above considerations, a concrete policy is needed in maintaining the function of the Gunungpati District, so that it can protect the ecosystem in its area. Besides the importance of providing education to the public regarding sustainable urban development, to create complex environmental preservation, this article contributes to the field of public management and a collaborative governance policy model that is directly implemented in the city of Semarang.